Advance : the ultimate how-to guide for your career - Burnison, Gary, 1961- (John Wiley & Sons, Inc., 2020)
"In his previous book, Lose the Resume, Land the Job, author Gary Burnison exposed the myths and the ineffective thinking around how to land the job you really want. Now, in Advance, Burnison takes readers through the next stage--advancing in their careers. Advance is extremely timely and topical in today's do-it-yourself career development world. Average job tenure has fallen to about four years on average and often only one or two years for younger professionals. These "career nomads" simply aren't around long enough to access career development from their employers. On the other end of the workplace spectrum, many employees find themselves stuck in one job without a promotion, without any raise to speak or, and with no opportunities to learn and grow. In Advance, Burnison lays out a mosaic of "how-to" advice that applies every day and at every level--the skills and behaviors that help people navigate their careers and stand out among the crowd. He takes on a "Top 20" of career must-haves: managing for the first time, engaging in the "money conversation" with your boss, dealing with difficult bosses (without quitting), coping with coworkers (without losing your mind), making presentations (that don't put people to sleep), mastering digital communication (and avoiding emails that will get you fired), thinking globally (without leaving your office), taking an overseas assignment, meeting senior leaders for the first time (without putting your foot in your mouth), navigating political waters (without sinking your career), reading and fitting in with the culture, and more"--